Designing Ethical Social Robots—A Longitudinal Field Study With Older Adults - van Maris, Anouk; Zook, Nancy; Caleb-Solly, Praminda; Studley, Matthew; Winfield, Alan; Dogramadzi, Sanja (Frontiers in Robotics and AI, 2020)
Emotional deception and emotional attachment are regarded as ethical concerns in human robot interaction. Considering these concerns is essential, particularly as little is known about longitudinal effects of interactions with social robots. We ran a longitudinal user study with older adults in two retirement villages, where people interacted with a robot in a didactic setting for eight sessions over a period of four weeks. The robot would show either non-emotive or emotive behavior during these interactions in order to investigate emotional deception. Questionnaires were given to investigate participants’ acceptance of the robot, perception of the social interactions with the robot and attachment to the robot. Results show that the robot’s behavior did not seem to influence participants’ acceptance of the robot, perception of the interaction or attachment to the robot. Time did not appear to influence participants’ level of attachment to the robot, which ranged from low to medium. The perceived ease of using the robot significantly increased over time. These findings indicate that a robot showing emotions (and perhaps resulting in users being deceived) in a didactic setting may not by default negatively influence participants’ acceptance and perception of the robot, and that older adults may not become distressed if the robot would break or be taken away from them, as attachment to the robot in this didactic setting was not high. However, more research is required as there may be other factors influencing these ethical concerns, and support through other measurements than questionnaires are required to be able to draw conclusions regarding these concerns.